nygṿdym vdrkhy hlymṿd shl ʾmṿrʾy nhrdʿʾ hʾḥrṿnym / Contrasting Study Methods of the Later Nehardians in the Babylonian Talmud - Cohen, Barak S. (Hebrew Union College annual, 2007)
In a few recent studies in talmudic history and methodology, I have pointed out a tendency among Babylonian amoraim to differ from one another in their techniques for interpreting literary sources. My analysis supports the idea that there were consistent styles of learning among Babylonian amoraim, styles of learning accurately portrayed in talmudic dialectics. Understanding the rabbinic legal mind aids in clarifying the foundations of their halakhic thought and sheds new light on certain difficult passages in the Talmud. This study presents a systematic analysis of the entire corpus of the traditions attributed to the later Nehardeans: אמרי נהרדעי "(the) Nehardeans say," Rav Hama, and Ameimar, who lived in the fourth and fifth centuries in Babylonia. This analysis reveals significant differences in their system of study, regarding their use and interpretation of antecedent literary sources (biblical, tannaitic or amoraic sources). The approach taken by "(the) Nehardeans say" deals mainly with formalistic features, a method which is based, consistently, on earlier literary sources. The legal method of Rav Hama and Ameimar, on the other hand, was far more "flexible" and lenient, with a tendency to take into consideration the conditions and circumstances of the specific case under discussion, even at the expense of deviating from the law as it appears in literary sources. Consequently, this allows for a reexamination of some of the conclusions in the existing research regarding the Nehardean legal methods.